Allocative efficiency of UK firms during the Great Recession - Florian Gerth (University of Kent, School of Economics, 2017)
This paper argues that the fall and persistently low level of UK Total Factor Productivity (TFP) following the Great Recession was caused by the turnover (entry and exit) of firms, rather than by resource misallocation between firms within industries. I conduct a misallocation exercise employing the Hsieh and Klenow (2009) and the Olley and Pakes (1996) methods using the FAME microlevel dataset that contains more than 9 million firms within the UK over the 2006 - 2014 period. The main findings are that, first, service sector TFP drops far more than manufacturing TFP and therefore drives the fall and long-lasting depression in aggregate productivity. Second, within-industry misallocation cannot account for the drop in TFP. Third, the entry and exit of firms both contribute to the decline in aggregate TFP while the entry of firms has a larger negative effect on TFP than the exit of firms. And fourth, the pattern of within-industry misallocation and firm dynamics is the same for the manufacturing and the service sector.
Keywords: D24; E13; E32; L11; 330; Great Recession in the UK; Factor Misallocation; FAME dataset